The Effect of Hands-on Practice on the Skills Proficiency of Nursing Home Nurses (International Journal of Studies in Nursing, 2020)
Background: The most recent nursing home regulations indicate that nurses must possess the skills sets needed to properly provide residents’ care (“Reform of Requirements,” 2016). Nursing home directors of nursing (DONs) frequently meet the requirement to train their nurses using online continuing education programs. However, the hands-on practice of fundamental clinical nursing skills necessary to maintain proficiency cannot be accomplished with this method. Purpose: This study aimed to determine whether an educational intervention including hands-on practice of two clinical skills would improve the skills proficiency of nursing home nurses. Method: The study used a pretest-posttest design with skills fair-style educational intervention for nursing home nurses recruited from two nursing homes. The pretest and posttest each included a multiple-choice quiz and hands-on demonstrations of two different clinical skills. Statistical analysis using paired t-tests showed significantly improved skills proficiency for the participating nurses following the educational intervention with hands-on practice of the two clinical skills. Findings: The findings suggest that nursing home DONs should consider educational interventions that include hands-on practice to maintain clinical skills proficiency.